Enhancing shielding efficiency of ordinary and barite concrete in radiation shielding utilizations - Nasuha Ahmad; Mohd Idzat Idris; Azimah Hussin; Julia Abdul Karim; N. M. Azreen; Rafidah Zainon (Scientific Reports, 2024)
Abstract Concrete has been widely utilized as a radiation shielding material due to its properties and structural integrity. This study aims to evaluate the efficiency of ordinary concrete versus barite concrete as radiation shielding materials, focusing on the physical aspects and changes in crystal size lattice parameters after neutron irradiation. Specifically, the research investigates the shielding effectiveness of these materials across different grades (M15, M25, M35, and M45) against gamma-ray sources Cobalt-60 and Caesium-137. The methodology involves measuring the linear attenuation coefficient (μ), half value layer (HVL), tenth value layer (TVL), and mean free path (MFP). Additionally, X-ray diffraction (XRD) was employed to assess crystallite size and lattice parameter changes post-irradiation for neutron irradiation. Results indicate that incorporating barite as an aggregate significantly enhances the density and crystallite macroscopic properties of the concrete. Irradiation with Cobalt-60 and Cesium 137 revealed that ordinary concrete has a lower linear attenuation (μ) ranging from 0.172 to 0.195 cm−1, with consistent mass attenuation across all grades at 0.81 cm2/g. XRD analysis demonstrated a rightward shift in the SiO₂ and BaSO₄ peaks post-irradiation, signifying crystalline expansion. In terms of lattice parameters, the d-value showed a notable decrease of 0.10 after 48 h of irradiation in grade 25, while the most significant increase of 0.02 occurred after 24 h of irradiation in grades 15 and 45. In conclusion, barite concrete proves to be more effective for radiation shielding in nuclear facilities, whereas ordinary concrete is suitable for medical shielding, or facilities exposed to lower radiation doses.